Parametric singular double phase Dirichlet problems - Bai Yunru; Papageorgiou Nikolaos S.; Zeng Shengda (Advances in Nonlinear Analysis, 2023)
We consider a parametric (with two parameters μ,λ>0μ ,λ \gt 0) Dirichlet problem driven by the double phase differential operator and a reaction which has the competing effect of a singular term and of a superlinear perturbation. We prove a bifurcation-type result in the parameter λ>0λ \gt 0, when the other parameter μ>0μ \gt 0 is large.